Cone-in-cone and beef mineralization associated with Triassic growth basin faulting and shallow shale diagenesis, Edgeoya, Svalbard - Maher H. D.; Ogata K.; Braathen A. (Geological Magazine, 2017)
Cone-in-cone (CIC) and beef (BF) carbonate lenses ornament detachment zone faults underlying Triassic growth basins on Edgeoya. Field relationships place CIC and BF growth as during early diagenesis and a transition from hydroplastic to a later brittle-style of faulting that is marked by coarser calcite veining. Deformation is constrained to have occurred at <300 m depth. Multiple models exist for CIC formation. For the Edgeoya example, textural analysis of thin-sections suggests that small tensile fractures and carbonate shell fragments nucleated development of calcite aggregates with CIC and BF morphology within unconsolidated to poorly consolidated sediment to form asymmetric antitaxial tensile aggregates subparallel to bedding and fault surfaces. The conical forms result from differential growth on stepped, cleavage-parallel faces of fibres facing host sediment, with preferential inclusion incorporation at inner corners. The preferred directions of calcite growth are attributed to local stresses and seepage flow associated with pore pressure gradients. Substantial framboidal pyrite in the sediments represents an early phase of microbially driven sulphate reduction, which may have induced calcite mineralization. The transition to brittle-style faulting was marked by development of deformation twins in CIC/BF fibres, and a transition to coarse, blocky calcite growth in relay arrays of steeply oriented microveins. This indicates local fault-related stresses substantially changed during shallow diagenesis and lithification, an evolution attributed to changing pore pressures, seepage forces and material moduli. Calcite mineralizations at Edgeoya track the very significant changes in mechanical properties and stress states that occur during synlithification deformation at very shallow crustal levels.